Water balance of Eucalyptus globulus and Quercus suber forest stands in south Portugal - PEREIRA DE ALMEIDA, A; RIEKERK, H (Forest ecology and management, 1990)
The study utilized two watersheds near the town of Odemira in Alentejo, a southern province of Portugal. The region has a relatively humid climate because of its proximity to the sea. One 6-ha watershed contained scattered native cork oak (Quercus suber) with a newly developing understory of shrubs. An adjacent 19-ha watershed contained a mature Eucalyptus globulus stand, which was harvested for the study. The study included measurements of precipitation, runoff and soil water storage. Measurements of the tree stands and canopies were included for the characterization of throughfall and stemflow
Keywords: Angiospermae; Anthropogenic factor; Arbol forestal frondoso; Arbre forestier feuillu; Artificial forest stand; Balance agua; Bilan eau; Bosque; Dicotyledones; Eucalyptus globulus; Europa; EUROPE; Facteur anthropique; Factor antrópico; Fagaceae; Forests; forêt; Hardwood forest tree; Mediterranean vegetation; Myrtaceae; Peuplement forestier artificiel; Poblamiento forestal artificial; Portugal; Quercus suber; Spermatophyta; Vegetación mediterránea; Végétation méditerranéenne; Water balance (citation)

Model for a new sylvo-pastoral system in the Mamora cork-oak forest - Montoya Oliver, Jose Miguel (Landscape and Urban Planning, 1986)
The Mamora cork forest (central Morocco), located on sandy soils in the Moroccan coastal plain where the climate is semiarid (annual rainfall, depending on the zone, in the range 400–600 mm) with very dry summers and temperate-warm winters, covers 60 000 ha and is the largest cork forest in the world. The trees in this forest are vital in that they protect and improve the pasture growing beneath them, as well as producing abundant fruit that can be eaten by livestock, and foliage which can serve as emergency feed. This, combined with its special geographic/regional location, makes Mamora an important pasturing area. It also produces some 40% of Moroccan cork and is therefore of great sylvicultural and industrial significance also, making it a sylvo-pastoral area of major economic and social importance at both regional and national levels.
Keywords: activité forestière; écologie; élevage; emploi; forêt; prairie; PVD (citation); utilisation du sol